Independensi Penegak Hukum Dan Pengawasan Preventif Dalam Penegakan Hukum Di Komisi Pemberantasan Korupsi Pasca Putusan Mahkamah Konstitusi Nomor 70/PUU-XVII/2019 - Manalu, Aimi Solidei; Siahaan, Samuel Fajar Hotmangara Tua (Jurnal Konstitusi & Demokrasi, 2022)
In 2021, the Constitutional Court issued Decision Number 70/PUU-XVII/2019, partially granting the petitioner's request for judicial review. The content of the decision includes emphasizing the independence of the Corruption Eradication Commission (KPK) and confirming the position of the Corruption Eradication Commission Supervisory Board in the Corruption Eradication Commission's law enforcement structure. However, following the issuance of the verdict, there are several imperfect legal gaps related to the position of the Corruption Eradication Commission. These legal gaps relate to the extent of the independence of the Corruption Eradication Commission when linked to the independence of the judicial power, as the Corruption Eradication Commission has been declared an institution related to the judicial power. In addition, the position of the Supervisory Board of the Corruption Eradication Commission is related to law enforcement in the Corruption Eradication Commission and the legal gap of absolute power in KPK wiretapping and seizure.